Relationship between Wood Properties and Developed Drying Schedule of Inferior Teak (Tectona grandis L.F) and Mahogany (Swietenia macrophylla King) - Tomy Listyanto; Ganis Lukmandaru; Candra Pramadya; Dwi Siswanto; Nobuaki Hattori (Masyarakat Peneliti Kayu Indonesia, 2010)
Development of drying schedule has been a critical issue on a drying process concerning the changing of material condition, especially in Java. Established drying schedule used to be purposed for a high quality timber. The aims of this study were to develop drying schedule of inferior teak and mahogany, and to analyze the relationship between the drying schedule and its wood properties.The specimens were taken from 25 years old teak and 20 years-old mahogany. Wood density, sapwood percentage and extractive contents were determined as wood properties. Four types of specimen’s dimensions (25 x 30 mm; 25 x 50 mm; 25 x 100 mm; and 50 x 50 mm) were dried in the oven with temperature of 103⁰C until reach oven dried conditions. Levels of checks, collapse, and honeycomb were observed to develop drying schedule. A Chi square analysis was used to analyze the relationship between wood properties and the drying schedule.The results showed that there were four types of drying schedule are applicable for teak and five types for mahogany. The most recommended schedule for teak sample was the schedule with an initial temperature (IT) was 70⁰C, relative humidity (RH) was 71%, and the final temperature (FT) was 90⁰C, while the mahogany wood was the schedule with an IT 60⁰C, RH 81%, and the FT 85⁰C, respectively. Chi square analysis indicated that the mahogany lumber dimension was significantly related to the schedule development while specific gravity, heartwood percentage, and extractive content had no significant relationship with the drying schedule development.